(untitled) (KULT_online, 2017)
What is the image to the narrative in film art? A good friend who provides support by visualizing the unfolding story? A bitter rival struggling for its own right to just be “art” without showing any regard for the narrative? In Telling Images Fabienne Liptay demonstrates by means of an interdisciplinary analysis of contemporary films that the relationship between moving image and filmic narration might not always be easy but can be productively renegotiated. Drawing on theoretical discourses in film studies, art theory, and history as well as narratology, the author shows, by means of filmic examples beyond classical Hollywood cinema, how the moving image may not only cooperate with storytelling strategies but also stake claim to aesthetic independence.